Coffees in Brazil: A bibliometric study about specialty coffees - Soares, Larissa Bergides; Dornelas , Myriam Angélica (Seven Editora, 2023)
Coffee is a beverage consumed daily worldwide, mainly by the western population, making it one of the most important beverages in the world. The production and agro-industrial chain of special coffee configures an infinite number of possibilities of action in the national and international market for the agents involved in this production chain. Based on this context, the general objective of this study was to conduct a bibliographic survey on the topic of the specialty coffee market in the Web of Science database, in the period 2017-2021. Methodologically, this study was classified as exploratory research, carried out through a bibliometric study. Data collection was performed on the Thomson Reuters Web of Science platform (main collection) due to the expanding number of journals indexed to it. A research protocol was created using keywords and then a filter by categories and refinement by the most cited articles was carried out. Data collection took place on October 28, 2021, which resulted in 150 articles for all areas of knowledge. We opted for the filter of categories related to the following areas of knowledge: Business, Agronomy, Management, Multidisciplinary Sciences and Economics, where it was obtained in 39 articles. The refinement of the search for the most cited articles resulted in five works on specialty coffees. Finally, this study managed to gather important information about the value chain, about consumers, about the market as a whole and about the relevance of associations, cooperatives, and certifiers, which help attest to the superiority of specialty coffees.DOI:https://doi.org/10.56238/alookdevelopv1-071